PENGARUH UKURAN KANTOR AKUNTAN PUBLIK, AUDIT TENURE, DAN FEE AUDIT TERHADAP KUALITAS AUDIT (Studi Empiris pada Perusahaan Sektor Consumer Non-Cyclicals Yang Terdaftar di Bursa Efek Indonesia Periode 2017-2020) - Aldina, Nadia Indri (Jurnal KIAFE, 2021)
This study aims to examine and analyze the effect of public accounting firm size, audit tenure and audit fees on audit quality. The population used in this study is the financial statements of non-cyclicals consumer sector companies listed on the Indonesia Stock Exchange during the 2017-2020 period. The sample selection in this study used a purposive sampling method, in order to obtain a sample of 33 companies that met the criteria in determining this sample, with 132 observations during 2017-2020. The audit quality in this study is calculated using the earnings surprise benchmark approach. The analytical method used in this study is logistic regression analysis using the IBM SPSS software version 25. The results of this study indicate that the size of the public accounting firm has no effect on audit quality, audit tenure has effect on audit quality, and audit fees has no effect on audit quality.Keywords: Public Accounting Firm Size, Audit Tenure, Audit Fee, Audit Quality.